Clinical and structural effects of dental bleaching - Petkova Gueorguieva de Rodríguez, Marieta (2005)
The aim of this study was to revise the recently scientific literature about risks of dental bleaching. It has been revised several articles which had for subject clínical and structural effects of tooth whitening. The principal clinical effects were tooth sensitivity and longevity of bleaching; as structural effects were seen enamel demineralization, decreasing in dentine hardness, modification of adherence capacity and morphology of macrophages and secretory capacity and proliferation of fibroblasts. In conclusion dental whitening is conservative procedure but have many risks to consider in dental treatment.